CULTURAL AND PRAGMATICAL ASPECT OF ADVERTISING - E.S. SHABAY (Advanced Engineering Research)
This article provides the analysis of the concept of «sign», gives an overview of main characteristics of «semiosphere», pointes out the ground of misunderstanding of cross-cultural adds; detenmines the types of signes and thein connection.